Anthropologie sceptique et modernité - Giocanti, Sylvia (La croisée des chemins, 2022)
Scepticism is a philosophical current in which doubt is neither a discomfort to be overcome, nor an artifice located at the beginning of an investigation aiming at its own overcoming, but a way of speaking and of standing in existence. What does such a position imply on the anthropological level? That contrary to those who have thought of doubt as a preparation for faith or for the refoundation of science, it is more natural to doubt than to believe? The chapters in this volume examine how modern sceptical doubt, born of its implementation in Montaigne's Essays, far from being a negative disposition of mind that leads to despair, has contributed to revalorizing opinion and belief in a regime of uncertainty, to rehabilitating the imagination and the senses, while promoting other uses of reason. The book is aimed at all readers who are interested in the renewal of the conception of philosophy through doubt, whether it be its discursive practices or its values. It also invites us to reflect on the link between the philosophical discourse on humanity and the human sciences, a link that the sceptical substitution of an anthropology of the relation to the metaphysical approach to humanity has made possible.